Thin-Entrance Window Process for Soft X-Ray Sensors - Segal, Julie; Kenney, Christopher; Kowalski, Jeffrey M.; Kowalski, Jeffrey E.; Blaj, Gabriel; Rozario, Lisa; Hasi, Jasmin; Dragone, Angelo; Caragiulo, Pietro; Rota, Lorenzo (Frontiers in Physics, 2021)
New free electron lasers, such as SLAC’s LCLS-II, will provide unique scientific imaging opportunities. In order to fully utilize these facilities, we need to develop detectors with shallow entrance windows that will enable detection of soft x-rays from 250eV-1.5KeV. Achieving adequately shallow entrance windows is challenging because the high temperature anneal needed to activate the dopant for the diode termination also drives the dopant profile deeper, growing the region that is insensitive to soft x-rays. A new microwave annealing technology provides an efficient way to achieve shallow entrance windows in fully depleted high-resistivity silicon sensors. The micro-wave anneal technique can activate dopants at low substrate temperature, with minimal dopant diffusion, and can be used to fabricate both n-type and p-type entrance windows. SRP and SIMS measurements were used to verify dopant activation with negligible dopant diffusion. We then applied the microwave anneal process to a planar sensor device wafer, using the new process to create the backside diode contact. Electrical test of the resulting sensors shows good reverse bias diode characteristics. The sensors have been bump-bonded to a read-out ASIC and used successfully to measure an Fe-55 x-ray spectrum. Process and device simulations were performed to characterize the quantum efficiency of the entrance window for soft x-rays. This technique is useful for other sensor applications requiring a shallow entrance window, including detectors for UV photons, low energy ions and low energy electrons.